The Madeiran plants collected by Sir Hans Sloane in 1687, and his descriptions - Sequeira, Miguel Menezes de (2010)
The Macaronesian Islands comprise the Atlantic archipelagos of Azores, Madeira, Selvagens, Canaries and Cape Verde. These islands were a major focus for plant exploration during the 17th and 18th centuries. Sir Hans Sloane (1660–1753), one of the most important patrons and sponsors of natural sciences and botanical research, visited Madeira on his way to Jamaica in 1687. Although he stayed in Madeira for only three days, he collected plant specimens of 38 taxa (including one brown alga) and made important observations concerning the flora and fauna of Madeira from near Funchal. Sixty-six polynomial names of plants from the island are recorded in Sloane’s published work along with 18 copperplate engravings, ostensibly from Madeira, although our study shows that only thirteen of them are of taxa occurring on the island. Fourteen of the sixty-six polynomials reported by Sloane relate to Macaronesian endemic taxa, six of them restricted to Madeira. Our study shows that nine of the fifteen polynomials that he putatively recorded for Madeira and/or the Antilles or for which he was unsure of their origin are from the West Indies and do not occur on this Macaronesian island. Two of the taxa that are listed for Madeira and the Carib bean Islands were likely to be present in both insular systems. Although there is evidence of earlier botanical explorations in Macaronesia, the herbarium collections made by Sloane in Madeira represent the earliest documented plant hunting expedition to Macaronesia, and Sir Hans Sloane can be considered as one of the pioneers of botanical exploration in these Atlantic Islands. Sloane’s records provide an early floristic study of a diverse island flora.